2020
DOI: 10.1177/0276236620905810
|View full text |Cite
|
Sign up to set email alerts
|

Looking Behind and Looking Ahead: Personality Differences in Counterfactual and Prefactual Thinking

Abstract: Counterfactual thinking (CFT) involves the mental simulation of alternatives to the past. In contrast, prefactual thinking (PFT) simulates potential outcomes that have yet to happen. Individuals differ in the extent to which they think in these ways, but we know little about how personality is implicated in these differences. This study investigated the relationship between Big Five personality traits and levels of spontaneous CFT and PFT embedded within a fictional diary entry. Results indicated that CFT was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Prefactuals are conditional propositions about what might occur in the future: If X occurs, then Y will occur (Epstude et al, 2016). Research in cognitive, social, developmental, and applied psychology has shown that the human ability to imagine different plausible futures—that is, prefactual thinking —plays important roles in goal pursuit, motivation, and affect regulation (Bacon et al, 2020; Bagozzi et al, 2004; Epstude et al, 2016; Goerke et al, 2004; Hammell & Chan, 2016; Scholl & Sassenberg, 2015). We propose, however, that prefactual thinking can have a darker consequence: encouraging people to excuse dishonesty.…”
Section: People Judge a Falsehood’s Morality Based On The Truthfulnes...mentioning
confidence: 99%
“…Prefactuals are conditional propositions about what might occur in the future: If X occurs, then Y will occur (Epstude et al, 2016). Research in cognitive, social, developmental, and applied psychology has shown that the human ability to imagine different plausible futures—that is, prefactual thinking —plays important roles in goal pursuit, motivation, and affect regulation (Bacon et al, 2020; Bagozzi et al, 2004; Epstude et al, 2016; Goerke et al, 2004; Hammell & Chan, 2016; Scholl & Sassenberg, 2015). We propose, however, that prefactual thinking can have a darker consequence: encouraging people to excuse dishonesty.…”
Section: People Judge a Falsehood’s Morality Based On The Truthfulnes...mentioning
confidence: 99%